Maintenance of Proteostasis by P Body-Mediated Regulation of eIF4E Availability during Aging in Caenorhabditis elegans - Rieckher, Matthias (Cell Rep, 2018)
Aging is accompanied by a pervasive collapse of proteostasis, while reducing general protein synthesis promotes longevity across taxa. Here, we show that the eIF4E isoform IFE-2 is increasingly sequestered in mRNA processing (P) bodies during aging and upon stress in Caenorhabditis elegans. Loss of the enhancer of mRNA decapping EDC-3 causes further entrapment of IFE-2 in P bodies and lowers protein synthesis rates in somatic tissues. Animals lacking EDC-3 are long lived and stress resistant, congruent with IFE-2-deficient mutants. Notably, neuron-specific expression of EDC-3 is sufficient to reverse lifespan extension, while sequestration of IFE-2 in neuronal P bodies counteracts age-related neuronal decline. The effects of mRNA decapping deficiency on stress resistance and longevity are orchestrated by a multimodal stress response involving the transcription factor SKN-1, which mediates lifespan extension upon reduced protein synthesis. Our findings elucidate a mechanism of proteostasis control during aging through P body-mediated regulation of protein synthesis in the soma.